Application of Machine Learning for Weather Forecasting Using Artificial Neural Networks - Kuppusamy, P; Jayalakshmi, K; Himavathi, C (International Journal of Computer Sciences and Engineering, 2025)
The weather forecasting has been prepared using the atmosphere condition manually. However, these estimations are unstable and imprecise for long duration. The machine learning is more robust compute the weather forecasting with precise prediction for long duration. This paper has proposed the Artificial Neural Networks (ANN) based model with supervised learning model in weather prediction. This proposed prototype is designed to predict different weather conditions with linear regression. This model is simulated with different dataset using supervised learning machine learning data repository. The proposed model performed better than traditional method in weather prediction. The atmosphere parameters such as temperature, pressure, dew, humidity are exploited to design, train and test a model. The future climate is predicted using machine learning by analyzing the parameters.